2020
DOI: 10.3390/cancers13010010
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the HOX Proteins in Cancer Invasion and Metastasis

Abstract: Invasion and metastasis correspond to the foremost cause of cancer-related death, and the molecular networks behind these two processes are extremely complex and dependent on the intra- and extracellular conditions along with the prime of the premetastatic niche. Currently, several studies suggest an association between the levels of HOX genes expression and cancer cell invasion and metastasis, which favour the formation of novel tumour masses. The deregulation of HOX genes by HMGA2/TET1 signalling and the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 166 publications
(193 reference statements)
0
24
0
1
Order By: Relevance
“…HOX genes, a highly conserved subgroup of the homologous box superfamily, play crucial roles in embryonic development ( 1 ). In mammals, HOX genes are divided into four clusters (HOXA, HOXB, HOXC, HOXD), which located on four different chromosomes (7p15, 17q21, 12q13, and 2q31) ( 2 ), with each cluster containing 9-11 members ( 3 ). To date, 39 HOX genes have been identified in mammals and are separated into 13 paralog groups according to the chromosomal position and sequence similarity in each cluster ( 4 ) ( Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HOX genes, a highly conserved subgroup of the homologous box superfamily, play crucial roles in embryonic development ( 1 ). In mammals, HOX genes are divided into four clusters (HOXA, HOXB, HOXC, HOXD), which located on four different chromosomes (7p15, 17q21, 12q13, and 2q31) ( 2 ), with each cluster containing 9-11 members ( 3 ). To date, 39 HOX genes have been identified in mammals and are separated into 13 paralog groups according to the chromosomal position and sequence similarity in each cluster ( 4 ) ( Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…HOX genes transcription usually occurs during the embryonic development and is lowly expressed in adult cells to participate in cell physiology ( 1 , 14 , 15 ). However, HOX genes re-expression occurs in different cancers and is associated with tumor initiation and progression ( 2 , 16 , 17 ). In recent decades, the roles of HOX genes in organogenesis and tumorigenesis have been studied in detail ( 1 , 2 , 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study a statistically significant strong positive correlation was found between SOX3 immunopositive structures in the patient epithelium and HOXB3 positive structures in the patient epithelium, and a statistically significant very strong positive correlation was found between SOX3 positive structures in patient epithelium and HOXB3 positive structures in patient connective tissue, which may indicate a possible interaction between these factors within cleftaffected tissue. HOXB3 has been described affecting the proliferation of different cell lineages with research mainly focused on HOXB3 role in development of different cancer types and formation of metastases [ 37 , 38 ]. This possible interaction between SOX3 and HOXB3 might be involved with the regulation of cell proliferation within the cleft affected tissue.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid and ever-evolving genomic sequencing technology-related development, a number of molecules were found to play important roles in different steps of metastasis; for example, alterations in the expression of E-cadherin and metalloproteinase 9 (MMP9), which are epithelial-mesenchymal transition (EMT) markers that play important roles in mediating tumor invasion and metastasis [40][41][42]; chemokine receptors including CXCR4 and CCR7, which play critical roles in mediating the infiltration of metastatic BC cells into the lung parenchyma and the homing of tumor cells to lung niches [43], and angiogenesis activators and inhibitors that regulate the blood supply to primary tumors and metastases [6,44,45]. Several new genes were identified that participate in TGF-β-induced EMT, including HOXB7, which can directly bind to the promoters of TGF-β2 [46]. Numerous earlier studies on BC metastasis restricted themselves to studying primary tumor tissues or often focused only on one individual gene of interest at a time; these approaches are too prone to bias to generate a comprehensive viewpoint of the molecular mechanisms regulating the metastasis cascade.…”
Section: Major Hypotheses On Metastasismentioning
confidence: 99%